Mesalazine, an osteopontin inhibitor: The potential prophylactic and remedial roles in induced liver fibrosis in rats. (1st June 2018) - Ramadan, A.; Afifi, Nehal; Yassin, Nemat Z.; Abdel-Rahman, Rehab F.; Abd El-Rahman, Sahar S.; Fayed, Hany M.
Abstract: Liver fibrosis is a major health issue leading to high morbidity and mortality. The potential anti-fibrotic activity and the effect of mesalazine on osteopontin (OPN), an extra cellular matrix (ECM) component were evaluated in TAA-induced liver fibrosis in rats. For this purpose, forty-two adult male Wistar rats were divided into six groups. All animals, except the normal control, were intraperitoneally injected with TAA (200 mg/kg) twice per week for 6 weeks. In the hepato-protective study, animals were administered mesalazine (50 and 100 mg/kg, orally) for 4 weeks before induction of liver fibrosis then concomitantly with TAA injection. In the hepato-therapeutic study, animals were administered mesalazine for 6 weeks after TAA discontinuation with the same doses. In both studies, mesalazine administration improved liver biomarkers through decreasing serum levels of AST, ALT and total bilirubin when compared to fibrotic group with significant increase in total protein and albumin levels. Mesalazine significantly decreased hepatic MDA level and counteracted the depletion of hepatic GSH content and SOD activity. Additionally, it limits the elevation of OPN and TGF-β1 concentrations and suppressed TNF-α as well as α-SMA levels in hepatic tissue homogenate. Histopathologically, mesalazine as a treatment showed a good restoration of the hepatic parenchymal cells with an obvious decreased intensity and retraction of fibrous proliferation, while as a prophylaxis it didn't achieve enough protection against the harmful effect of TAA, although it decreased the intensity of portal to portal fibrosis and pseudolobulation. Furthermore, mesalazine could suppress the expression of both α-SMA and caspase-3 in immunohistochemical sections. In conclusion, mesalazine could have a potential new indication as anti-fibrotic agent through limiting the oxidative damage and altering TNF-ɑ pathway as an anti-inflammatory drug with down-regulating TGF-β1, OPN, α-SMA and caspase-3 signaling pathways. Highlights: Mesalazine is a promising anti-fibrotic candidate in liver fibrosis in a rat. Mesalazine could have a substantial restorative effect on the hepatic cells. Mesalazine down-regulates TGF-β1, OPN, α-SMA and caspase-3 signaling pathways.